1982
DOI: 10.1002/mrd.1120050311
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of the head of ctenomys maulinus spermatozoon with special reference to the nucleus

Abstract: The spermatozoa of the neotropical hystricomorph rodent Ctenomys maulinus have been examined cytochemically and under the transmission electron microscope. The head is flattened dorsoventrally. At the caudal end of the head there is a process oriented parallel to the tail. This process corresponds to a cylindrical extension of the nucleus, which constitutes a unique feature among mammals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…(Plate Ib). As previously described for other species (Feito & Gallardo, 1976, sperm heads were paddle-like, with a nuclear caudal extension originating at the base of the head at the opposite side of the insertion of the flagellum. Little variation was also found within this group with respect to the general morphological pattern and linear dimensions of spermatozoa ( Table I).…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…(Plate Ib). As previously described for other species (Feito & Gallardo, 1976, sperm heads were paddle-like, with a nuclear caudal extension originating at the base of the head at the opposite side of the insertion of the flagellum. Little variation was also found within this group with respect to the general morphological pattern and linear dimensions of spermatozoa ( Table I).…”
Section: Resultsmentioning
confidence: 59%
“…In a progress report , a preliminary survey of the sperm morphology of several species of Ctenomys showed that the genus could be divided into two groups of species bearing symmetrical or asymmetrical sperm cells according to the absence or presence of the nuclear caudal extension. As originally pointed out by Feito & Gallardo (1976), the study of additional species of Ctenomys and other Octodontidae would help to understand the morphofunctional and evolutionary meaning of this structure. We report here new information on the morphometrics of sperm cells in species of the genus Ctenomys distributed in Argentina and Paraguay, with the description of a new morphological type.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The species examined by Sage et al (1986) and by this study barely overlap, so little can be concluded about this discrepancy. (2) Similarly, species with asymmetric sperm (Feito and Barros, 1982) do not form a monophyletic group in our most parsimonious trees, that rather place them in two groups (haigi ϩ sociabilis separate from mendocinus), but this separation is weakly supported. Additional species with asymmetric sperm must be considered to address this issue.…”
Section: Figmentioning
confidence: 86%
“…Gallardo, 1982;Vitullo et al, 1988;Vitullo and Cook, 1991). The asymmetric sperm, first described by Feito and Barros (1982), is characterized by a paddle-like head with a postacrosomic process that originates at the base of the head opposite the insertion of the flagellum (Fig. 5b).…”
Section: Multiple Origins Of the Asymmetric Sperm Morphmentioning
confidence: 99%